Dinamika Sosial dalam Praktik Informal di Workshop Otomotif: Studi Kasus tentang Peran Kepercayaan dalam Wanprestasi di Kabupaten Sleman - Suwardi, Suwardi; Winadi, Enrico (Sahabat Akademia Group, 2025)
This study explores the social dynamics underlying transactional practices in automotive workshops in Sleman Regency, Indonesia, with particular attention to cases of breach of agreement (wanprestasi). While previous studies typically approach such issues from a legal standpoint, this research offers a sociological perspective by examining how trust, informal relationships, and communication shape service exchanges. Using a qualitative case study method, data were collected through interviews with workshop owners, technicians, and customers, as well as participant observation and document analysis at three independent workshops. Thematic analysis revealed that interactions between service providers and customers are largely governed by social capital built through repeated engagements. Breaches of agreement are not seen merely as technical failures but as disruptions in socially negotiated expectations. In response, service providers employ adaptive strategies—such as informal compensation, flexible communication, and reliance on personal reputation—to restore trust and maintain customer loyalty. The findings highlight how informal conflict resolution mechanisms operate within community-based service economies and emphasize the continued relevance of trust theory and social capital in understanding economic transactions beyond formal contractual frameworks. This study suggests that business sustainability in the informal sector depends heavily on relationship-building and reputation management. Future research could explore similar dynamics in other informal service sectors or examine how digital technologies reshape trust-building processes.